Local avifauna: a tool for conservation, ecotourism and environmental education - Perdomo, Oscar; Salazar-Báez, Pilar; Fernández-L, Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Photographic records of animal species in their environment have been widely used by researchers for species identification and ecological studies. In this study, we used photography as a tool to record and identify birds of the municipality of Páez, Boyacá, located in the Llanos foothills, with a landscape dominated by cloud forests, pastures and crops. We photographed and identified 133 bird species in roads and footpaths of the municipality; we found that the families Tyrannidae and Thraupidae, and the genus Tangara had the highest species diversity. All species reported here are in the Least Concern category of the International Union for Conservation of Nature, and 11 are migratory. The bird diversity of the municipality has a great potential for sustainable use. We report local common names for 63.16% of the registered species, and the sighting of 73.68% of these birds, identified with help from the community. In consequence, we propose further scientific research to assess the ecosystem services provided by birds and the use of the diversity and attractiveness of the avifauna to establish ecotouristic programs that promote the development of local communities.